Exploring emerging psychopathological characteristics and challenges of novel depression subtypes: insights from the literature - Chiappini, Stefania; Sampogna, Gaia; Ventriglio, Antonio; Menculini, Giulia; Ricci, Valerio; Pettorruso, Mauro; Volpe, Umberto; Martinotti, Giovanni (Frontiers in Psychiatry, 2025)
BackgroundDepression is a widespread global health issue, significantly impacting all areas of life and is a leading cause of disability. Societal changes, including technological and cultural shifts, and the emergence of new psychoactive substances, have influenced how depression manifests, introducing new clinical dimensions and challenges in its understanding and treatment.SummaryThis review summarizes from a psychopathological and clinical point of view the most important features related to novel depression subtypes, specifically: I) Early-onset depression; II) Depression and social disconnection; III) Depression and Alcohol/Substance Use Disorder; IV) Depression and Gender Dysphoria; V) Depression, stressful events, and other environmental factors. For each domain, the available research evidence is summarized, starting from theoretical contributions to the relevant psychopathological descriptors with special attention to issues relevant for the clinical practice.Key MessagesOverall, the phenomenology of depression is currently enriched by new symptomatology entities, including the dimensions of boredom, shame, fatigue, alexithymia, and emotional dysregulation. Those symptoms prevail in different novel subtypes of depression deserving in the clinical practice special attention and focused interventions.